(untitled) (Journal of Rangpur Medical College, 2023)
Background: Suicide is a worldwide growing but neglected problem crossing culture, geographies, religious, social and economic boundaries. Suicide is a perplexing phenomenon of taking one’s own life. As versatile human beings are, reasons behind suicide attempts are also unique. There is paucity of study on the clinical characteristics of these patients from a psychosocial and psychiatric point in Bangladesh. Objective: The study was aimed to assess the socio-demographic profile and psychiatric morbidity in attempted suicide patients. Methods: This cross-sectional observational study was carried out for 4 months (May’2017-September’2017) at the Rangpur Medical College Hospital, Rangpur, Bangladesh. ). A total of 101 patients were purposively selected from the patients with suicidal attempt from different departments of the hospital (Medicine, Surgery, Head-Neck & Otorhinolaryngology). Informed written consent was obtained from all patients. The interview was conducted once the patient was considered fit for a psychosocial assessment using a semi-structured questionnaire and clinical interviews. Diagnosis was made according to DSM-IV. Data was entered and analyzed using SPSS version 24 and results were expressed as proportions and percentages. Results: The majority of suicide attempts seen are in socio-economically-deprived young persons. Majority were <20 years age (41.59%), Female (53.47%), Unmarried (51.49%), Rural dwellers(72.28%), students (38.62%) and 58% attempts were impulsive. 63% without any prior suicidal thoughts, 56% resorted to poisoning, 49% attempted due to domestic quarrel, 65% suffered from a psychiatric disorder and major depressive disorder (18%) was found to be one of the commonest diagnosed disorders. Conclusion: Psychiatric disorders and their co morbidities are common in suicide attempt patients which calls for implementation of hospital guidelines for routine psychiatric and psychosocial assessments. J Rang Med Col. September 2023; Vol. 8, No. 2: 7-13